RESPONS TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) TERHADAP PUPUK UREA, SP36, dan KCL DOSIS - Jamaludin Jamaludin; Krisnarini Krisnarini (Jurnal WACANA PERTANIAN, 2020)
Sweet corn is one of the agricultural commodities that is widely consumed because it contains various nutrients that are needed by the human body. Sweet corn production is strongly influenced by several things, including the adequacy of nutrients in the soil. To meet the needs of plant nutrients can be done through fertilization activities. The effectiveness of fertilization is strongly influenced by the dose, type, method and time of application. This study aims to determine the growth and yield of sweet corn plants due to the application of Urea, SP36, and KCl  fertilizers with different doses. The results showed that the treatment using Urea, SP36, and KCl fertilizers with different doses had a significant effect on the variables of plant height, weight of cobs with beans, and weight of cobs without beans. However, there was no significant difference in the number of leaves, ear diameter, dissolved solids, and yield per hectare